Occurrence of herpesvirus in fish - Bergmann, Sven Michael; Wang, Yingying; Li, Yingying; Wang, Qing; Klafack, Sandro; Jin, Yeonhwa; Hofmann, Arndt Christian; Kiełpińska, Jolanta; Becker, Anna; Zeng, Weiwei (Journal of Veterinary Research, 2024)
Introduction: Herpesviruses are common agents in animals of the aquatic environment. They infect many species of fish but only lead to disease in one or two species. Nevertheless, infected fish without clinical symptoms can actively transfer infectious agents to disease-susceptible species. The aim of the study was to identify and prove the natural presence of different herpesviruses. Material and Methods: Koi, Nile tilapia, grass carp, goldfish and crucian carp were infected with a herpesvirus isolate 99% identical to goldfish herpesvirus (GHV) or cyprinid herpesvirus 2 (CyHV-2) obtained from crucian carp. Before and after infection, samples were collected non-lethally at different time points from all five fish species to identify and evaluate the replication of viruses naturally infecting the fish as well as the CyHV-2 experimentally infecting them. Gill swabs and separated leukocytes were subjected to PCR and the results compared. Results: These samples yielded DNA of koi herpesvirus (KHV, also referred to as CyHV-3), GHV and a new herpesvirus. While Asian-lineage CyHV-3 DNA was detected in samples from crucian carp and goldfish, CyHV-2 DNA was found in samples from koi and tilapia. A new, hitherto unknown herpesvirus was identified in samples from grass carp, and was confirmed by nested PCR and sequence analysis. The survival rates were 5% for grass carp, 30% for tilapia, 55% for crucian carp, 70% for koi and 100% for goldfish at 20 days post infection. Evolutionary analyses were conducted and five clusters were visible: CyHV-1 (carp pox virus), CyHV-2 with sequences from koi and tilapia, CyHV-3 with sequences from crucian carp and goldfish, probable CyHV-4 from sichel and a newly discovered herpesvirus - CyHV-5 - from grass carp. Conclusion: The results obtained with the molecular tools as well as from the animal experiment demonstrated the pluripotency of aquatic herpesviruses to infect different fish species with and without visible clinical signs or mortality.
CRIS-Team Scopus Importer:2024-05-31
Keywords: clinical signs; fish; herpesviruses